Pengaruh Penggunaan Media Geogebra terhadap Motivasi dan Hasil Belajar Matematika Siswa - Tia Purnama; Aniswita Aniswita; Imamuddin Imamuddin; Tasnim Rahmat (Departement of Mathematics Education, 2024)
The background of the research was the problems that occur in class IX Putri Pondok Pesantren Sumatra Thawalib Parabek, namely the lack of innovation in the use of learning media, there is no technology-based learning media, low motivation and student learning outcomes in learning mathematics. The low student learning outcomes in mathematics are indicated by the fact that most of students are still not able to reach the KKM, namely 80. With a percentage of 73.67% of students who have not been able to reach the KKM. This can be seen in the percentage of completeness of PTS learning outcomes in class IX Putri Pondok Pesantren Sumatra Thawalib Parabek. To overcome this problem, researcher conducted research using Geogebra media as a learning media. The type of research used was experimental research with The Static Group Comparison Design. The population in this study were all students of class IX Putri Pondok Pesantren Sumatra Thawalib Parabek for the 2022/2023 academic year. Sampling was done by random sampling technique. The selected samples were students of class IX.7 as the experimental class and class IX.10 as the control class. The research data were obtained from a questionnaire on students' motivation to learn mathematics and tests of students' mathematics learning outcomes. From the results of the questionnaire analysis of student learning motivation using the t test and Minitab software with a = 0.05, tcount > ttable is obtained, namely 1.85598 > 1.67866 and Pvalue < 0.05, namely 0.035 < 0.05 so reject H0 . The results of the analysis of student mathematics learning outcomes tests using the t test and Minitab software with a = 0.05, obtained tcount > ttable, namely 1.956 > 1.67866 and Pvalue <0.05, namely 0.029 <0.05 so reject H0. Therefore, it can be concluded that learning using Geogebra media has a significant influence on students’ motivations and mathematics learning outcomes compared learning without using Geogebra media.